ANALISIS DAN PERANCANGAN CLUSTERING SISWA BARU MENGGUNAKAN METODE K-MEANS PADA SMK NEGERI 1 KOTA JAMBI - Tandy, Juliana; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2019)
Every year there will be students who continue education to the next stage, including at SMK Negeri 1Kota Jambi, Event admission of new students is done every 1 year, in the selection process and receptionrequires the application of more efficient is to use the application, change the system Manual into thesystem computerized and perform a new grouping students by majors at SMK Negeri 1 Kota Jambinamely Computer Engineering and Networks, Accounting, Office Administration and Marketing.Therefore Final report with the title " Analysis and design of Clustering New Students Using the K-MeansMethod at SMK Negeri 1 Kota Jambi ". The purpose of writing this thesis report is to determine the newadmissions system and a new grouping students by majors at SMK Negeri 1 Kota Jambi. In writing thisreport require student data, the data value of national examination results, majors available, and studentadmission quotas. The results obtained by the registrant data reports, reports on the screening of newstudents by quotas, and the results of grouping students who have been in the selection. Results beobtained as a function of weight for admission of new students each school year and make an efficientwork system for the school.